New public management reform in European countries: The retreat of the state from telecommunication services - Carina Schmitt; Philipp B. Schuster (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2010)
In the post war period, telecommunications - being services of 'general economic interest' - were initially managed by public administrative bodies in many Western European countries. With the rise of New Public Management (NPM) in the 1980s, these bodies were often transformed into public corporations or joint stock companies. Following corporatisation, the provision and the management of these services of general economic interest was gradually transferred to private actors. This paper analyses whether privatisation, as part of NPM reforms, has benefited the consumer. We have, therefore, compiled data on privatisation in the telecommunication sector for 15 European countries from 1980 to 2006. The data set covers the corporatisation process, as well as the transfer of the service provision to the private sector. Three empirical findings stand out: first, the reform processes have differed widely from each other. Second, it's not just the transfer of ownership to the private sector that has ensured efficiency gains and increased consumer benefits; corporatisation has done this as well. Third, efficiency gains have been transferred to the consumer, especially at the beginning of the reform process. – – In der Nachkriegszeit wurden Telekommunikationsdienstleistungen in vielen westeuropäischen Ländern zumeist von Verwaltungseinheiten bereitgestellt. Mit dem Aufkommen des New Public Managements (NPMs) in den 1980er Jahren wurden diese Verwaltungseinheiten in öffentlich-rechtliche Unternehmen oder Aktiengesellschaften umgewandelt (=formelle Privatisierung) und anschließend stückweise an private Akteure übertragen (=materielle Privatisierung). Dieser Beitrag untersucht, ob die Konsumenten von diesen Privatisierungsmaßnahmen profitieren konnten. Zur Beantwortung dieser Frage wurde ein vollständig neuer Paneldatensatz zusammengestellt, mit dem die Privatisierung im Telekommunikationssektor für 15 europäische Länder von 1980 bis 2006 abgebildet werden kann. Der Datensatz umfasst erstmals sowohl formelle als auch materielle Privatisierungsschritte. Drei empirische Ergebnisse sind besonders hervorzuheben. Erstens, der Privatisierungsprozess unterscheidet sich teilweise erheblich zwischen den Ländern. Zweitens, die Konsumenten konnten nicht nur vom Verkauf von Unternehmensanteilen profitieren, sondern auch von formellen Privatisierungsmaßnahmen. Drittens, Effizienzgewinne wurden insbesondere am Anfang des Reformprozesses an die Konsumenten weitergegeben.
Keywords: 330; Telekommunikation; Privatisierung; Verwaltungsreform; New Public Management; Wirtschaftliche Effizienz; Konsumentenrente; Europa